PROFIL PEKERJA ANAK (STUDI KASUS DI KOTA BANDA ACEH) - sufratul Aini; Muhammad Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractThis research purposes to examine the profile of child labor (Case Study in Banda Aceh City), using purposive sampling method, by sharing enquettes to 45 informants (child workers). Data processing is done with Microsoft Office Excel program. The results of this research indicate that the majority of the child laborers in Banda Aceh City are children whose daily status is as students. They beg after school. This work activities do can have both positive and negative effects. The positive effect is that income from work can be saved for daily necessities such as allowance, school necessities and ease the burden on the family. While the negative effect is that children are exploited or their growth and development are stunted, so that they cannot be optimal of physically, mentally, socially and intellectually.Keywords: Child Labor, Employment and Poverty.